Phytochemical Screening and Toxicological Evaluation Using Brine Shrimp Lethality Test (BSLT) of Some Fractions of Prasman Leaves (Eupatorium triplinerve V) Extract - Shirly Kumala; Dwi Windi Sapitri (Indonesian Society for Cancer Chemoprevention, 2011)
Prasman leaves (Eupatororium triplinerve V) was well documented to have anti cancer benefit in Indonesian traditional medicine history. However, there were no scientific studies including toxicological assessment on the plan extract. The purpose of this study was to investigate the toxicological effect of some fractions of Prasman leaves methanol extract. Phytochemical screening by the Farnsworth method on powder and some fraction of the methanol extract were conducted followed by toxicity test using the “Brine Shrimp Lethality” test (BSLT) method. In the current study results, the phytochemical screening showed the presence of flavonoid, saponin, coumarin, tannin, steroid and volatile oil. LC50 of the n-hexane fraction 238.66 µg/mL, ethyl acetate fraction 24.42 µg/mL, and n-butanol 64.10 µg/mL.Keywords : BSLT, Toxicity test, Eupatororium triplinerve